1987
DOI: 10.1093/nar/15.21.9104
|View full text |Cite
|
Sign up to set email alerts
|

RFLP of the human placental alkaline phosphatase gene (PLAP)

Abstract: SOURCE AND DESCRIPTION OF CLONE: ALP-1, a 1.1 kb EcoRI/ApaI fragment of a PLAP cDNA subcloned into pBR322 from a XgtlO cDNA library of the cell line HEp-2 (Martin et al., 1987). POLYMORPHISM: RsaI identifies a two allele polymorphism with polymorphic bands at 1.6 kb and 1.8 kb as well as a constant band at 2.2 kb (Figure). TaqI reveals a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
6
1
Order By: Relevance
“…The Southern blot revealed polymor phic bands at 1.6 and 1.8-kb as described earlier by Martin et al [14] and constant bands at 2.4, 2.2, 1.3, 1.2 and 1.1 kb. The three Rsal genotypes are shown in figure 1.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The Southern blot revealed polymor phic bands at 1.6 and 1.8-kb as described earlier by Martin et al [14] and constant bands at 2.4, 2.2, 1.3, 1.2 and 1.1 kb. The three Rsal genotypes are shown in figure 1.…”
Section: Resultssupporting
confidence: 80%
“…Table 1 shows the relationship between the Rsal genotypes and the electropho retic PLAP phenotypes. The frequencies of the 1.6 (Al)-and 1.8 (A2)-kb alleles were 0.46 and 0.54, respectively, which is not significantly different from the fre quencies (0.38 and 0.63) found by Martin et al [14] in 20 European Whites. The ob served distribution of Rsal genotypes showed no significant departure from the expected distribution assuming a Hardy-Weinberg equilibrium (x: = 2.54, p>0.05).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Martin et al [14] found poly morphic DNA fragments after cleavage with Rsal. In a series of 20 European Whites the frequencies of the 1.6-kb (Al) and 1.8-kb (A2) alleles were 0.38 and 0.63, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…By means of starch gel electrophore sis of placental extracts and histochemical staining, three common alleles (1,2 and 3 [or S. F and 1 in older nomenclature]) and a large number of rare alleles have been discovered [9][10][11]. Additional genetic variation has been found using immunochemical methods [12,13], and on the DNA level restriction fragment length polymorphisms (RFLPs) of PLAP have been found after cleavage with Pstl [14,15] and Rsal [16]. Genetic polymorphism has also been detected in GCAP using immunochem ical methods [17] and restriction enzyme anal ysis [18,19].…”
Section: Introductionmentioning
confidence: 99%